Mortalidade por causas externas: análise da ocorrência no período de 2008 a 2012 na microrregião de saúde de Franca – SP - Gimenes, Vanda Maria (2014)
External causes, that are traumas, injuries or any other damages to health, whether intentional or not, sudden start and as an immediate consequence of violence or other hexogen cause, figure as important issue in collective health field, acquiring an epidemic character and turning into one of the most serious Public Health problem in the world. In Brazil, external causes represents the third most frequent cause of death, however, in many areas it already represents the second cause of death, showing a growing tendency. The present study aimed to identify the mortality profile by external causes in the health micro region o Franca - SP. For so, we opted for a retrospective quantitative and descriptive study. The scenario of the study was the micro region of Franca, made up by 22 cities. The data collection was through SIM/DATASUS information, referring to the period of 2008-2012. For statistic data analysis, we opted for Qui-square and Odds Ratio essays. Results pointed out to a balance in distribution of deaths by external causes, that the deaths by such causes were more frequent in male individuals, in the age group of 20-59 years old, with education ignored, followed by those between 4-7 years old of studies, afro descendent, single, and the most common cause of death are transportation accidents. Results make evident the statistically significant difference in deaths by external causes among male individuals, and among those afro descendant ones. It was concluded that the data surveyed, may subside awareness and prevention politics to violence causes, contributing this way to health promotion to the studied population. Keywords: mortality, external causes, information system on mortality.